Evaluación de la resistencia y/o tolerancia de 24 variedades de papas nativas al parasitismo del nematodo del quiste de la papa (Globodera pallida) en invernadero Cutuglahua - Pichincha 2009 - Riera Suárez, Wilson Iván (2009)
The cultivation of the potato is one of the most important, since it is source of carbohydrates inside the diet of the Ecuadorians, the consumption per capitals is of 25kg annual, also in the 2006 he/she was considered a sowed surface of 52000ha with a yield average 6.8t/ha these low yields they are influenced by factors biotic and abiotic. Inside the factors biotic he/she is the nematodes of the potato cyst (Globodera pallida) considered as a plague that reduces the yield until in 30% in their first year, they are especially in most of areas mumps in the county of Tungurahua where they meet the biggest infestation levels with populations that overcome the 100 eggs and larva / gram of floor, taking into account that the balance level is of 10 eggs and larva / gram of floor depending the susceptibility of the varieties.